Birds - Frost, Helen (Mankato, Minn. : Pebble Books, 2000)
Simple text and photographs present the features and care of birds that can be kept as pets.
Includes index.
Includes glossary.
Includes bibliography.
K-3
AR Accelerated Reader
Keywords: Birds as pets